Chlorella sp. (UKM8), A Local Microalgae Isolate with Anti-Human Herpes Virus and Antioxidant Properties - Shaima, Abdul Fattah; Mohd Yasin, Nazlina Haiza; Ibrahim, Nazlina (Malaysian Applied Biology, 2022)
Microalgae are an invaluable source of new and safe therapeutics with potential antiviral and free-radical scavenging compounds. This study aimed to investigate the antiviral and antioxidant properties of local microalgae, Chlorella sp. (UKM8). The UKM8 methanol extract (UKM8-ME) was tested for antiviral activity using plaque reduction assay against Human Herpes Virus type 1 (HHV-1). The antioxidant activity of UKM8-ME was evaluated for the radical scavenging activity (RSA) according to the elimination of 1,1-diphenyl-2-pikrilhydrazil (DPPH) radicals and total phenolic content (TPC) by the Folin-Ciocalteu reactions. UKM8-ME effective concentration that inhibits 50% (EC50) of plaque formation was 222.33 ± 24.54 μg/mL. The calculated selective index is 19 indicating potential antiviral activity. In the DPPH assay, the IC50 value of positive control and UKM8-ME were 122.9 ± 29.1 and 198.78 ± 14.35 μg/mL, respectively. The TPC of positive control and UKM8-ME were 263.414 ± 9.6 and 254.793 ± 3.31 mg GAE/g, respectively. Evaluation in RSA and TPC concludes that UKM8-ME has high antioxidant activity. In conclusion, UKM8-ME has two unique properties in anti-HHV-1 and antioxidant activities that can be further evaluated for potential in pharmaceutics and food ingredients.